A Meta-Analysis for Effects of Elevated Pre-Transplantation Serum Ferritin on the Outcomes in Patients Undergoing Hematopoietic Stem Cell Transplantation. (8th August 2016) - Guo, Wenjian; Dong, Aishu; He, Muqing; Lin, Xiaoji; Yao, Rongxing; Zhu, Baolin; Pan, Xiahui; Jie, Jin
ABSTRACT: The level of pre-transplantation serum ferritin (SF) is one of the factors related to outcome for patients undergoing allogeneic hematopoietic stem cell transplantation. We searched PubMed and Cochrane Library databases from 2000 to 2014. The primary efficacy outcome was overall survival rate and non-relapse mortality. Twenty clinical trials were selected from 189 studies identified. The combined hazard ratio indicated a significantly lower overall survival rate and a higher non-relapse mortality rate in patients with elevated SF before transplantation. This indicates that elevated pre-transplantation SF affects outcome in patients undergoing allogeneic hematopoietic stem cell transplantation.